2021
DOI: 10.1002/jdn.10085
|View full text |Cite
|
Sign up to set email alerts
|

Immune function changes of the IDPN‐induced Tourette syndrome rat model

Abstract: There may be immunologic alternations during Tourette syndrome (TS) development. This study aimed to determine the immune function changes in different aspects (spleen or thymus index, plasma cytokines, and T cell) in an 3,3′‐iminodipropionitrile (IDPN)‐induced rat model of TS. Male Sprague‐Dawley rats were assigned to control and TS groups. The control group received intraperitoneal infections of normal saline (5 ml kg−1 day−1), and the TS rats were injected with IDPN (150 mg kg−1 day−1). The spleen and thymu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Our study showed that the rat model of TS with DA dysregulation constructed using IDPN had significantly higher cytokines like IL-6 and TNF-α in the brain than in the normal group. The present data confirmed and extended prior findings that TS rats were associated with increased cytokines expression ( Long et al, 2019b ; Liu et al, 2020 ). Long et al (2019a) also found highly elevated cytokines in a TS model constructed using the 5-hydroxytryptamine agonist 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study showed that the rat model of TS with DA dysregulation constructed using IDPN had significantly higher cytokines like IL-6 and TNF-α in the brain than in the normal group. The present data confirmed and extended prior findings that TS rats were associated with increased cytokines expression ( Long et al, 2019b ; Liu et al, 2020 ). Long et al (2019a) also found highly elevated cytokines in a TS model constructed using the 5-hydroxytryptamine agonist 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI).…”
Section: Discussionsupporting
confidence: 92%
“…These results support the existence of a link between immunity dysfunction and behavioral stereotypes. The TS animal models [ours and previous studies (Long et al, 2019a,b;Liu et al, 2020)] constructed by neurotransmitter dysfunction showed increased cytokines, which may also indicate an interaction between neurotransmitters and neuroinflammation in TS disorders. Animal models constructed by IDPN mainly lead to a decrease in DA neurotransmission (Nobuo Wakata, 2000), and some studies have found that decreased CNS DA leads to increased neurological inflammation (Pajares et al, 2020).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…3,3′-Iminodipropionitrile (IDPN) is a synthetic organic nitrile, and it is the most commonly used inducer of TS in animal models as its effects can last a long time ( Wang et al, 2013 , 2021 ; Zhang et al, 2014 ; Zhang and Li, 2015a , b ; Xie et al, 2016 ; Chen et al, 2019 ; Zhao et al, 2020 ; Liu et al, 2021 ). Our previous research results also showed that IDPN induced abnormal stereotyped behavior in mice ( Lin et al, 2019 ), which caused a behavioral syndrome in rodents similar to the symptoms of patients with TS, such as featuring lateral and vertical head-shakes, random circling, hyperactivity, and elevated acoustic startle response ( Khan and Ibrahim, 2015 ; Zhang and Li, 2015c ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%